PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN AUDIO VISUAL TERHADAP PERILAKU IBU POSTPARTUM DALAM MANAJEMEN LAKTASI - Inge Anggi Anggarini (IKesT Muhammadiyah Palembang, 2024)
Introduction: The low coverage of breastfeeding, especially exclusive breastfeeding, is caused by several factors including the low knowledge of mothers about the benefits of breastfeeding and proper breastfeeding methods, lack of lactation counseling services, lack of support from health workers, socio-cultural perceptions against breastfeeding, working mothers and Formula milk marketing influences the thinking of mothers and health workers. Method: This study uses a quantitative approach, the method used in this study is a quasi-experimental with the type of one-group pre test design.. Results: the Wilcoxon signed ranks test showed that there were significant differences before and after the intervention was carried out on the two dependent variables with p-value = 0.001. This shows that there is a significant influence between the Effect of Health Education Using Audio Visual Media on the Behavior of Postpartum Mothers in Lactation Management. Discussion: Providing audio-visual education on the behavior of postpartum mothers in lactation management is one of the efforts to increase the coverage of exclusive breastfeeding and reduce morbidity (illness) rates in infants. Keywords: health education, audio visual, knowledge, attitude, lactation management